Employee Engagement and Psychological Well-Being on Employee Loyalty through Organizational Citizenship Behavior (OCB) - Syidah Syidah; Mahmud Mahmud; Desi Rubiyanti (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This research aims to analyze the effect of employee engagement and psychological well-being on employee loyalty through organizational citizenship behavior (OCB) as a mediating variable at Hotel Aman Gati and Any Lestari. Research Method: A quantitative approach was employed using a total sampling technique involving 45 operational employees. Data were collected via Likert-scale questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) through SmartPLS. Results and Discussion: The findings reveal that both employee engagement and psychological well-being have a positive and significant direct impact on employee loyalty and OCB. Furthermore, OCB serves as a significant mediator, linking work engagement, psychological well-being, and long-term employee loyalty. Implications: Hotel management should develop strategic policies that support mental well-being and active engagement to retain human resources sustainably. Future research is recommended to increase sample sizes, include additional hotel tiers, and explore additional variables such as organizational culture. Originality: This study provides originality by empirically confirming the mediating role of OCB within the specific and rarely studied context of a local-scale hospitality ecosystem.